WEBSITE APPLICATIONS WWW.PENDIDIKAN-DAMAI.ORG WITH PHP AND THE SMARTY TEMPLATE ENGINE - Andi Pramono; Yulina Yulina, SKom, MMSi (Jurnal Sistem Informasi, 2008)
On Scientific Writing is the author discusses the use of PHP and the Smarty TemplateEngine to display a separate website to view the PHP source itself and the HTML todisplay the website, which supports dynamic website as an information media,namely as a means to retrieve, process, and provide information with effective.The discussion starts with the introduction of PHP, how sususan form and language,and explain what is provided by PHP and how a web interface is presented using theSmarty Template Engine.